2011
DOI: 10.1503/cjs.028509
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric surgeon's 35-year experience with pilonidal disease in a Canadian children's hospital

Abstract: Background:There is an ongoing debate regarding the optimal surgical management for pilonidal disease in the pediatric population. The purpose of this study was to evaluate a pediatric surgeon's experience at a Canadian children's hospital over 35 years. Methods:We performed a retrospective review of the charts of patients seen and treated from July 1969 to December 2003, inclusive. All patients were evaluated for age, sex, clinical diagnosis, infection, treatment, healing time, complications and results.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 14 publications
(28 reference statements)
6
36
1
1
Order By: Relevance
“…NPWT also requires home nursing or frequent visits to outpatient centers to change dressings, as well as the inconvenience of carrying an external device. In this study, mean time to complete healing compares favorably with reported mean healing times for wet-to-dry [4,13] and NPWT [14,15] after pilonidal resection in adolescents and adults. (Table 2) The reported mean healing time for adult open pilonidal wounds treated with MatriStem was nearly identical at 52 days [9].…”
Section: Discussionsupporting
confidence: 66%
“…NPWT also requires home nursing or frequent visits to outpatient centers to change dressings, as well as the inconvenience of carrying an external device. In this study, mean time to complete healing compares favorably with reported mean healing times for wet-to-dry [4,13] and NPWT [14,15] after pilonidal resection in adolescents and adults. (Table 2) The reported mean healing time for adult open pilonidal wounds treated with MatriStem was nearly identical at 52 days [9].…”
Section: Discussionsupporting
confidence: 66%
“…3 During a telephone interview, the patients treated with surgical excision and LE expressed frustration with the number of emergency department procedures (e.g, incision and drainage, multiple courses of antibiotics). This frustra tion prompted them to explore various treatment options, which could account for the increased recurrence rates among these patients compared with those who were satis fied with observation.…”
Section: Discussion En Chirurgiementioning
confidence: 99%
“…5 It has also been established that once a pilonidal sinus recurs, the patient is more likely to keep experiencing recurrences, with decreasing time intervals in between. 3 Telephone followup revealed that some patients who had been referred for LE declined to pursue this treatment owing to cost. In London, Ont., the average cost for 1 LE treatment is $150, and the average participant needed 9.5 treatments over several weeks.…”
Section: Discussion En Chirurgiementioning
confidence: 99%
See 1 more Smart Citation
“…Although little has been reported concerning pediatric populations, SPS is a common entity amongst children and adolescents, with complication and recurrence rates similar to the adult population [1,5].…”
mentioning
confidence: 99%